Understanding Health Professional Responses to Service Disinvestment: A Qualitative Study - Mitchell, Deb (Int J Health Policy Manag, 2019)
Background: Disinvestment from inefficient health services may be a potential solution to rising healthcare costs, but there has been poor uptake of disinvestment recommendations. This Australian study aims to understand how health professionals react when confronted with a plan to disinvest from a health service they previously provided to their patients. Methods: This qualitative study took place prior to the disinvestment phase of a trial which removed weekend allied health services from acute hospital wards, to evaluate the effectiveness and cost effectiveness of the service. Observations and focus groups were used to collect data from 156 participants which was analysed thematically. Results: Initial reactions to the disinvestment were almost universally negative, with staff extremely concerned about the impact on the safety and quality of patient care and planning ways to circumvent the trial. Removal of existing services was perceived as a loss and created a direct threat to some clinicians’ professional identity. With time, discussion, and understanding of the project’s context, some staff moved towards acceptance and perceived the trial as an opportunity, particularly given the service was to be reinstated after the disinvestment. Conclusion: Clinicians and health service managers are protective of the services they deliver and can create barriers to disinvestment. Even when services are removed to ascertain their value, health professionals may continue to provide services to their patients. Measuring the impact of the disinvestment may assist staff to accept the removal of a service.